'The Office Boy's Triumph': Deceit and Display in early Twentieth-Century Wolverhampton. (2nd January 2017) - Benson, John
Abstract : The aim of this article is to explore the relationship between office work, spending and respectability in early twentieth-century England. It does so by focusing upon the 'Varley affair', a case in which an employee of Wolverhampton Council defrauded the Corporation of almost £85, 000 between 1905 and 1917. It is argued both that offices were not necessarily as tightly controlled as we have been led to believe, and that it was possible for office workers – provided they had sufficient funds – to spend their way to a solid, respectable standing in local middle-class society.